China's National Plan on Sustainable Implementation of the 2030 Development Goals: from the Perspective of National Performance of Multilateral Environmental Agreements - Qin Tianbao; Fang Hou (Vasyl Stefanyk Precarpathian National University, 2018)
In terms of the implementation of Multilateral Environmental Agreements, the implementation of the agreements has gradually shifted from the institutional construction of the international level to the implementation of the national level. Since the Millennium Development Goals did not reach the goal of sustainable development in the year of 2015, 2030 Sustainable Development Goals had drew the lessons, put forward the goals of economic, social and environmental, and required all countries to provide their own country's plan. As the largest developing country, China plays a decisive role in the international environmental governance. At home, China has formulated the domestic environmental governance norms for the implementation of the 2030 Sustainable Development Goals, and established an inter ministerial coordination mechanism for implementing the Sustainable Development Agenda composed of 43 government departments. China is also actively participating in international environmental governance, participating and promoting the conclusion and effectiveness of treaties on environmental protection at the international and regional levels, earnestly implementing and helping other countries to implement treaties, and expanding the global partnership through various formal and informal meetings and other channels.